Desire, Capital, Race and History at K Sello Duiker and Ishtiyaq Shukri’s Cape - Morar, Rowan (School of Languages and Literatures, 2019)
Traits of post-independence disillusionment registered in African literature areapparent in the post-apartheid work of K Sello Duiker and Ishtiyaq Shukri. Duiker’s The Quiet Violence of Dreams (2001) and Shukri’s The Silent Minaret (2005), in particular, represent the aftermath of unfulfilled expectations in postapartheid South Africa by focusing on the existential problems of their protagonists at the intersection of desire, capital, race and history at the Cape. In scenes from The Quiet Violence of Dreams, the protagonist Tshepo experiences racism at Cape Town’s gay clubs and bars, as well as the upmarket massage-parlour-brothel that he works for, a place initially brimming with the possibility of sexual and racial utopia. Disillusioned with the liberatory promise of a ‘gay identity’ and its unfulfilled expectations, he walks away from the predominantly white city centre, the wealthiest parts of the city, deliriously ambling his way to the outskirts of the city where the impoverished black majority live. Arriving in the township, a space where black people were forced to live during apartheid, outside of the central city and suburban districts that remain ostensibly white, he finds waste, dirt, and evil in the external world of the township that becomes indistinguishable from his mental world at times. The complex mixture of space and subject is the product of the historical racism, capitalist exclusion and the limits of desire that make Cape Town a hostile space, a sociality of exclusion. Identifying and analysing the processes and practices that produce the types of exclusion experienced by Tshepo, as well as the possibilities that arise from these situations, are the primary interests of this dissertation.